Are We Driven? Critical Theory and Psychoanalysis Reconsidered. Issue 4 (November 2015) - Allen, Amy
Abstract : If, as Axel Honneth has recently argued, critical theory needs psychoanalysis for meta-normative and explanatory reasons, this does not settle the question of which version of psychoanalysis critical theorists should embrace. In this paper, I argue against Honneth's favoured version – an intersubjectivist interpretation of Winnicott's object-relations theory – and in favour of an alternative based on the drive-theoretical work of Melanie Klein. Klein's work, I argue, provides critical theorists with a more realistic conception of the person and a richer explanatory account of human aggression and destructiveness than does Honneth's intersubjectivist view. As such, it better serves the ends for which Honneth claims that critical theory should turn to psychoanalysis in the first place.